2016
DOI: 10.3389/fmats.2016.00001
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Glass Compositions in Fly Ash

Abstract: In this study, four Class F fly ashes were studied with a scanning electron microscope; the glassy phases were identified and their compositions quantified using point compositional analysis with k-means clustering and multispectral image analysis. The results showed that while the bulk oxide contents of the fly ashes were different, the four fly ashes had somewhat similar glassy phase compositions. Aluminosilicate (AS) glasses, calcium aluminosilicate (CAS) glasses, a mixed glass, and, in one case, a high iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 20 publications
(30 reference statements)
1
18
0
Order By: Relevance
“…The micrographs on a 10-µ m scale clearly revealed particles' spherical shape for all fly ashes (Figure 3). EDS analysis confirmed that, in RFA and CFA, those particles were mostly built with silica and aluminum compounds typical for glassy aluminosilicates [56]. In BFA, particles were characterized by phosphate, calcium, and potassium compounds present in archerite, which is shown in the BFA structure by XRD.…”
Section: Sem Analysismentioning
confidence: 63%
“…The micrographs on a 10-µ m scale clearly revealed particles' spherical shape for all fly ashes (Figure 3). EDS analysis confirmed that, in RFA and CFA, those particles were mostly built with silica and aluminum compounds typical for glassy aluminosilicates [56]. In BFA, particles were characterized by phosphate, calcium, and potassium compounds present in archerite, which is shown in the BFA structure by XRD.…”
Section: Sem Analysismentioning
confidence: 63%
“…Another avenue of research that is relevant for fly ashes and slag is the investigation of the reactivity of glasses present in these materials. Fly ashes contain a variety of glassy phases, mostly modified aluminosilicates [58]. Both calcium and aluminum are important network modifiers in glasses that affect reactivity [59].…”
Section: By-product Materials: Ashes and Glassmentioning
confidence: 99%
“…X-Ray Diffraction, Scanning Electron Microscope, and Back Scattered Electron-Energy Dispersive X-Ray Spectroscopy Test of Geopolymers XRD SEM and BSE-EDS were used to test the factors including microstructure, mineral composition, and gel composition which affects the microscopic characteristics of fly ash-based geopolymers. Followed the test method mentioned in the literature (Aughenbaugh et al, 2016), each set of proportions in Table 4 was made into the 20 mm × 20 mm × 80 mm samples, and cured under the same curing conditions. The XRD test samples were taken from the non-carbonized zone in paste sample corresponding to D2.…”
Section: Methodsmentioning
confidence: 99%